2019
DOI: 10.1080/21691401.2019.1613420
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of miR-15a regulating the growth and apoptosis of human knee joint chondrocytes by targeting SMAD2

Abstract: Objective: To investigate the effects of miR-15a on proliferation and apoptosis of human knee articular chondrocytes and explore its underlying mechanism. Methods: qRT-PCR was used to detect the expression of miR-15a in normal chondrocytes and knee arthritic chondrocytes; miR-con (transfected miR-con), miR-15a (transfected miR-15a mimics), anti-miRcon group (transfected anti-miR-con), anti-miR-15a group (transfected anti-miR-15a mimics), pcDNA group (transfected pcDNA), pcDNA-SMAD2 group (transfected pcDNA-SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Recent research reported that the interaction between lncRNA and miRNA can modulate the expression of downstream genes and affect different biological functions [29][30][31][32]. To identify lncRNA that regulate miR-124-3p signaling, we used starBase v2.0 software to predict the lncRNA-miRNA interaction.…”
Section: Mir-124-3p Is Down-regulated By Its Cerna-linc00511mentioning
confidence: 99%
“…Recent research reported that the interaction between lncRNA and miRNA can modulate the expression of downstream genes and affect different biological functions [29][30][31][32]. To identify lncRNA that regulate miR-124-3p signaling, we used starBase v2.0 software to predict the lncRNA-miRNA interaction.…”
Section: Mir-124-3p Is Down-regulated By Its Cerna-linc00511mentioning
confidence: 99%
“… [ 108 , 109 ] Lipofectamine TM 2000 kit miR-15a Targeting SMAD2 In vitro Human normal chondrocytes Inhibiting the proliferation and promoting apoptosis of knee arthritis chondrocytes. [ 110 ] Lipo2000 microRNA-143-3p Targeting BMPR2 In vitro BMSCs MiR-143-3p could regulate the differentiation process by targeting BMPR2 in BMSCs. [ 111 ] DSPE-PEG-maleimide/ HAP-1 peptide Prednisone / immunosuppressive peptide CP Targeting Synovial; Targeting Inflammation In vitro & vivo Synovial fibroblast like and endothelial cells; Rats Targeted liposomes specifically bound to rabbit FLS and human FLS and showed a 7–10 folds increase in vivo localization in affected joints compared to unaffected joints.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…The targeting agents can be loaded into the liposomes. This strategy typically targets protein receptors or genes, such as CGS21680 (adenosine A2A receptor agonist), 108 , 109 miR-15a (a microRNA that silences SMAD2 gene expression), 110 and microRNA-143-3p (targeted regulation of BMPR2 expression). 111 The stable lipid bilayer structure of liposomes can help transport sensitive cargo into cells and enhance the effect of the agents.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%